2020
DOI: 10.1007/s10482-020-01486-3
|View full text |Cite
|
Sign up to set email alerts
|

Updates to the recently introduced family Lacipirellulaceae in the phylum Planctomycetes: isolation of strains belonging to the novel genera Aeoliella, Botrimarina, Pirellulimonas and Pseudobythopirellula and the novel species Bythopirellula polymerisocia and Posidoniimonas corsicana

Abstract: Eight novel strains of the phylum Planctomycetes were isolated from different aquatic habitats. Among these habitats were the hydrothermal vent system close to Panarea Island, a public beach at Mallorca Island, the shore of Costa Brava (Spain), and three sites with brackish water in the Baltic Sea. The genome sizes of the novel strains range from 4.33 to 6.29 Mb with DNA G+C contents between 52.8 and 66.7%. All strains are mesophilic (Topt 24–30 °C) and display generation times between 17 and 94 h. All eight i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Nevertheless, the first two described planctomycetal isolates from macroalgae belong to the class Phycisphaerae [ 24 , 25 , 26 ]. In recent years, single-cell genomes [ 27 ] and axenic cultures from macroalgae were also obtained for the families Pirellulaceae [ 28 , 29 , 30 , 31 ], Lacipirellulaceae [ 32 ], Planctomycetaceae [ 33 , 34 , 35 ], and Isosphaeraceae [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the first two described planctomycetal isolates from macroalgae belong to the class Phycisphaerae [ 24 , 25 , 26 ]. In recent years, single-cell genomes [ 27 ] and axenic cultures from macroalgae were also obtained for the families Pirellulaceae [ 28 , 29 , 30 , 31 ], Lacipirellulaceae [ 32 ], Planctomycetaceae [ 33 , 34 , 35 ], and Isosphaeraceae [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the partial 16S rRNA gene sequence placed strain ICT_H6.2 T into the family Lacipirellulaceae , order Pirellulales , class Planctomycetia , phylum Planctomycetota . Its closest type strain is the only described species of the genus Aeoliella , Aeoliella mucimassa Pan181 T [27], with 98.2 % similarity of the 16S rRNA gene, which is below the threshold proposed for species delineation (98.7 %) [37]. The 16S rRNA gene based phylogenetic tree showed that strain ICT_H6.2 T clusters in the family Lacipirellulaceae near strain Pan181 T but forms a separate branch.…”
Section: Partial 16s Rrna Gene Sequence-based Phylogenymentioning
confidence: 99%
“…Growth occurred at 10–37 °C (optimal, 20–30 °C), 0.5–4.0% NaCl (w/v) and pH 6.5–10.0 (optimal, pH 6.5–9.0), overall similar to A. mucimassa Pan181 T [27] (although no data is available regarding its salinity range). Utilized carbon sources (0.1 % w/v) consisted of dextran, arabinose, xylose, cellobiose, mannitol, lactose, galactose, fructose and glucose.…”
Section: Ecology Morphology and Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…13 The effective publication states that the type strain was also deposited as ATCC BAA-1503, but no documentation was supplied. 14 Denitrificimonas caeni Saati-Santamaría et al 2021 is a later homotypic synonym of Thiopseudomonas caeni Rudra and Gupta 2021. 15 The effective publication states that the type strain was also deposited as CCTCC AB208156 and KCTC 22292, but no documentation was supplied.…”
mentioning
confidence: 99%